Competitive interactions between weedy rice and cultivated rice as a function of added nitrogen and the level of competition - Chauhan, Bhagirath S.; Johnson, David E. (Wiley, 2011)
The competitive outcomes between weedy rice from Malaysia (MWR), the Philippines (PWR), and Vietnam (VWR) and cultivated rice (IR64) grown in pots were evaluated in a replacement series experiment with added N (0, 50, 100, and 150 kg N ha−1) and competition with IR64 plants (no competition, eight weedy rice plants : 0 IR64 plants; low competition, six weedy rice plants : two IR64 plants; and high competition, two weedy rice plants : six IR64 plants). The growth observations were taken at 10 weeks after sowing. When grown in a monoculture (no competition with IR64 plants), the PWR plants had a lower shoot biomass across N rates than did the MWR and VWR plants. The leaf area and shoot biomass of weedy rice across populations significantly increased with an increase in the N application rate. Each weedy rice population and the IR64 population showed linear responses of the leaf area and shoot biomass to the N rate at all levels of competition. The weedy rice and IR64 plants, when grown without competition, had a similar rate of response in the shoot biomass to the N rate. However, when grown in competition, the response to the added N varied among the weedy rice populations. The MWR plants under competition produced a similar amount of shoot biomass to the IR64 plants per unit addition of N. In contrast, the PWR and VWR populations under competition produced a greater amount of shoot biomass with each additional unit of N, compared to the IR64 population. The results illustrate that N fertilizer management might affect the outcome of weedy rice competition. This information could be incorporated into weedy rice management strategies.